Unfolding of a rectangular cloth from unarranged starting shapes by a Dual-Armed robot with a mechanism for managing recognition error and uncertainty. (19th May 2017) - Yuba, Hiroyuki; Arnold, Solvi; Yamazaki, Kimitoshi
Graphical Abstract: Abstract : We propose a method for unfolding a rectangular cloth placed on a table in an arbitrary unarranged shape, using a dual arm robot. There are many situations where the manipulation of fabric products by dual arm robots is slow due to operation complexity. Also, observation of fabric products in unarranged shapes can be fraught with uncertainty, posing further difficulties for robotic manipulation. In this article, we address these problems for our specific task, implementing a 'pinch and slide motion' to address the former issue, and an operation selection mechanism implemented as a partially observable Markov decision process to address the latter. We used this approach to let a robot unfold a rectangular cloth, thereby experimentally verifying the effectiveness of our approach.